Insects - Riehecky, Janet, 1953-; Gai, Jackie (2017)
Say hello to bees, ants, butterflies, and more! Insects is a colorful photo-filled animal-science reference book for young readers and browsers. Not only will kids discover basic topics such as habitat, anatomy, and diet, but they'll also find fun topics such record-breaking insects and how insects help people--all written in a clear, concise way.
What are insects? -- Part by part -- Common groups -- Circle of life -- A place to call home -- Working together -- Let's eat -- Sensing the world -- Move it! -- Staying safe -- Helpful insects -- Not-so-helpful insects -- Insect records -- Fun facts.
Includes bibliographical references.
Ages 4-8.
K to grade 3.
Keywords: Insects -- Juvenile literature; Insects -- Encyclopedias, Juvenile